ANALISA PENGARUH COUNTRY OF ORIGIN IMAGE DAN BRAND EQUITY DIMENSIONS TERHADAP BRAND EQUITY - Golan Hasan (Journal of Accounting and Management Innovation, 2018)
The main objective of this study is to examine how the country of origin image can influence the brand equity.This study aims to analyze the relationship between variables Country of origin image, brand equity dimensions that consisting  Brand Distinctiveness, Brand Loyalty, and Brand Awareness to the Brand Equity.                 This Research was conducted  with worker and college student who using smartphone in batam. Data was collected by distributing questionnaire to 300 respondent directly. The data processing using Structural Equation Model ( SEM ) Smart PLS (Partial Least Square) 3.0. Program.                The result showed intervening variables Country of origin image, brand equity dimensions that consisting  Brand Distinctiveness, Brand Loyalty, dan Brand Awareness have a significant effect on Brand Equity